The Influence of Ethylene Gas Concentration on LDPE/C2H4 Hybrid Explosion Process and its Severity - H., Badli; Siti Zubaidah, Sulaiman; M. N., Arifin; N., Semawi; Izirwan, Izhab; Siti Hajar Noor, Shaarani; Rohaida, Che Man; Siti Kholijah, Abdul Mudalip; I., Arshad (IOP Publishing, 2020)
The influence of ethylene (C2H4) gas concentration on the LDPE dust hybrid explosion in a 20-L spherical vessel, equipped with a chemical ignitor was analysed for the determination of maximum explosion overpressure, Pmax and deflagration index, KG. The LDPEC2H4 dust hybrid explosibility was evaluated based on the Pmax development, measured by the Kistler piezoelectric pressure transducer. The adiabatic flame temperature was calculated based on ideal gas law. It is speculated that the LDPE/C2H4 explosion undergoes three-phase process, starting with the ignition, followed by flame growth and flame regression. The highest Pmax (17.9 bar) and flame temperature (5200 K) was obtained at flame growth phase, recorded at C2H4 concentration of 3 vol/vol%. It was found that the Pmax and flame temperature is dependent on C2H4 concentration. The calculated KG values in a range of 14 – 60 bar.m/ms obtained in this study, suggesting that the LDPE/C2H4 dust hybrid explosion might subject to an extreme explosion characteristic.